2020
DOI: 10.1155/2020/8864323
|View full text |Cite
|
Sign up to set email alerts
|

AT1R/GSK-3β/mTOR Signaling Pathway Involved in Angiotensin II-Induced Neuronal Apoptosis after HIE Both In Vitro and In Vivo

Abstract: Objective. The focus of the present study is to evaluate the effects of Angiotensin II (Ang II) on neuronal apoptosis after HIE and the potential underlying mechanisms. Methods. Primary neonatal rat cortical neurons were used to study the oxygen-glucose deprivation (OGD) cell model. The expressions of Ang II, AT1R, GSK-3β, p-GSK-3β, mTOR, p-mTOR, Bax, Bcl-2, and cleaved caspase-3 were detected via western blot. IF and flow cytometry were used to evaluate neuronal apoptosis. Hypoxic-ischemic encephalopathy (HIE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…We used FJC (Chemicon, Temecula, CA, USA), which can specifically stain degenerating neurons in the CNS subject to various neurotoxin insults and neurological diseases [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used FJC (Chemicon, Temecula, CA, USA), which can specifically stain degenerating neurons in the CNS subject to various neurotoxin insults and neurological diseases [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Brain sections containing the hippocampus were prepared as in Section 2.9 . FJC staining was carried out using the following standard procedures [ 35 , 36 ]: (1) pretreatment with an alcohol-sodium hydroxide mixture. The sections were immersed in a solution containing 1% sodium hydroxide in 80% alcohol for 5 min, followed by 70% alcohol and distilled water each for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…Mouse model studies showed that nicotine exposure reduces angiotensin II type 2 receptor expression in the developing brain, increasing the vulnerability to HIE injury in neonates [ 22 ]. Angiotensin-II-induced neuronal apoptosis can also be observed through the mTOR signaling pathway after HIE [ 30 ]. However, a single marker approach might not explain the genetic reasons for a complex condition such as HIE, and an integrated genomic analysis needs to be conducted to identify markers leading to brain injury.…”
Section: Genomicsmentioning
confidence: 99%
“…Western blot was performed as described previously (Li et al, 2020;Si et al, 2020). The whole-cell lysate was prepared using M-PER Protein Extraction Reagent (Pierce, Rockford, IL, United States) supplemented with protease inhibitor cocktail.…”
Section: Western Blotmentioning
confidence: 99%